'Social Mix' and Neighbourhood Revitalization in a Transatlantic Perspective: Comparing Local Policy Discourses and Expectations in Paris (France), Bristol (UK) and Montréal (Canada). (18th June 2012) - Rose, Damaris; Germain, Annick; Bacqué, Marie‐Hélène; Bridge, Gary; Fijalkow, Yankel; Slater, Tom
<x xml:space="preserve">Abstract</x> Abstract The longstanding debate around the merits of promoting social class mix in urban neighbourhoods has taken a new twist in recent times. A transatlantic and neoliberal convergence of policy advice, supported by the 'neighbourhood effects' thesis, makes a case for addressing deep poverty by spatially deconcentrating it, inter alia, by gentrification. While developing trenchant critiques of this approach, critical urban scholarship has tended to take a 'top‐down' view of urban neoliberalism, giving insufficient consideration to the agency of local governance actors in policy design and implementation, as well as to differences in national and local reference points with regard to what social mix connotes. We present findings of a comparative study of the meanings and effects attributed to social mix by key local policy actors across three 'distressed' neighbourhoods: in inner‐city Paris (France), Bristol (UK) and Montréal (Canada), targeted for neighbourhood revitalization involving planned residential social mix in two cases and diversification of local retailing and its consumer base in all three. We find that while local actors' rationales for social mix do reflect a neoliberal turn, this is not embraced unequivocally and a strong home‐grown element, drawing on national or local 'myths', persists. Our study sheds light on the expectations that local policy actors have on the incoming middle classes to make the mix 'work' by supporting community; pointing to the paradoxes and limitations of such a perspective. Résumé Le débat déjà ancien sur l'intérêt de promouvoir la mixité sociale dans les quartiers urbains vient de connaître un revirement. Une convergence transatlantique et néolibérale des orientations politiques, soutenue par la thèse des 'effets de proximité', préconise de remédier à la grande pauvreté par une déconcentration spatiale, notamment via la gentrification. Tout en étant très critiques à l'égard de cette approche, les auteurs de recherches urbaines ont plutôt favorisé une vision du néolibéralisme urbain imposée d'en haut, négligeant en partie l'agence des acteurs de la gouvernance locale dans la conception et l'application des politiques, ainsi que les différences de repères nationaux et locaux dans ce qu'évoque la mixité sociale. Les résultats présentés émanent d'une étude comparative des significations et effets attribués à la mixité sociale par les principaux acteurs de l'action publique dans trois quartiers 'sinistrés' du centre‐ville de Paris, Bristol et Montréal, ceux‐ci faisant l'objet d'une revitalisation dans laquelle s'inscrivent la mixité sociale de l'espace résidentiel pour deux d'entre eux, et la diversification des commerces de proximité et de leur clientèle dans les trois cas. Si la justification de la mixité sociale par les acteurs locaux reflète effectivement un virage néolibéral, elle n'est pas adoptée sans hésitations, et une forte composante spécifique au lieu persiste, née de 'mythes' nationaux ou locaux. L'étude éclaire sur ce que les acteurs de la politique locale attendent des nouveaux habitants issus des classes moyennes pour que le mélange 'prenne' grâce à leur soutien à la communauté; elle met ainsi le doigt sur les paradoxes et limites de ce genre de perspective.